Islamic Studies in South Africa (American Journal of Islam and Society, 1994)
Background of South African IslamIn 1994, South Africans will celebrate three centuries of Islam inSouth Africa. Credit for establishing Islam in South Africa is usuallygiven to Sheikh Yusuf, a Macasser prince who was exiled to South Africafor leading the resistance against the Dutch colonization of Malaysia. Thefitst Muslims in South Africa, however, were actually slaves who hadbeen imported, beginning in 1677, mainly from India, the Indonesianarchipelago, Malaysia, and Sri Lanka, by the Dutch colonists living in theCape. The Cape Muslim community, popularly but inaccurately knownas "Malays" and known under apattheid as "Coloreds," is the oldest Muslimcommunity in South Africa. The other major Muslim community wasestablished over a century later by indentured laborers and tradespeoplefrom northern India, a minority of whom weae Muslims. The majority ofSouth African Indian Muslims, classified as "Asians" or "Asiatics," nowlive in Natal and Tramvaal. The third ethnically identifiable group, classifiedas "Aftican" or "Black," consists mainly of converts or theirdescendants. Of the entire South African Muslim population, roughly 49percent are "Coloreds," nearly 47 pement are "Asians," and, although statisticsregarding "Africans" ate generally unreliable, it is estimated thatthey are less than 4 percent. Less than 1 percent is "White."Contributions to South African SocietyAlthough Muslims make up less that 2 petcent of the total population,their presence is highly visible. There ate over twenty-five mosques inCape Town and over one hundred in Johannesburg, making minarets asfamiliar as church towers Many are histotic and/or architectuml monuments.More importantly, Muslims ate uniquely involved in the nation'scultwe and economy. The oldest extant Afrikaans-language manuscriptsare in the Arabic script, for they ate the work of Muslim slaves writingin the Dutch patois. South African historian Achrnat Davids has tracedmany linguistic elements of Afrikaans, both in vocabulary and grammar,to the influence of the Cape Muslims. Economically, the Indian Muslimsaxe the most affluent, owing primarily to the cirmmstances under whichthey came to South Africa. Muslim names on businesses and buildingsare a familiar sight in all major cities and on those UniveAty campusesthat non-Whites were allowed to attend during apartheid ...